Morphological and Morphometric Characteristics of the Kidneys and Testes of 6-Month-Old Rats Under Combined Deficiency Conditions - R. R. Baymuradov; Sh. J. Teshayev (American Journal of Bioscience and Clinical Integrity, 2026)
This study investigated the morphological and morphometric changes in the kidneys and testes of 6-month-old rats under conditions of combined deficiency of Zn, Se, Mg, and Fe trace elements. The results demonstrated pronounced dystrophic changes in the glomerular and tubular apparatus of the kidneys, structural remodeling of the filtration barrier, and interstitial remodeling processes. In the testes, marked thinning of the spermatogenic epithelium, reduction in germ cell population, decreased number of Leydig cells, and development of interstitial fibrosis were observed. The Johnsen scoring system confirmed a significant suppression of spermatogenesis. The obtained data indicate that combined trace element deficiency leads to severe structural and functional remodeling of both reproductive and excretory systems through oxidative stress and trophic disturbances.